Human Creativity in the Context of Creativity of God in Gen 1–2 - Pikor, Wojciech (The Biblical Annals, 2022)
In the biblical perspective, stories about the creation of the world in Gen 1–2 remain to be the basis to a discussion about human creativity. The premise of the text – creation of man “in the image of God” – makes us assume that, according to the Bible, creativity of man is to be the image of God’s creativity. Verification of this thesis goes from presenting history of interpretation of the biblical idea, namely creation of man “in the image of God,” then points to the need of analyzing the narrative of this phrase. Since the image of God presented in Gen 1 is not descriptive, the second part of the paper examines the way God reveals himself in this text through his creative action. The key to God’s creativity is his word of creation which he uses to differentiate created beings and establish relationships among them in order to build harmony in the newly founded world. The final part of the paper focuses on the analysis of verbs which in Gen 1–2 refer to human creativity; those verbs also point to their possible association with words as instruments for creating, organizing and arranging reality shaped by man. Following that comes the conclusion that God’s creativity is extended into creativity of man who was made “in the image of God.”